Peningkatan Kemampuan Mengenal Lambang Bilangan Menggunakan Media Loose Parts - Atmilawati, Windy; Arkam, Rohmad; Mustikasari, Rizki (MENTARI: Jurnal Pendidikan Anak Usia Dini, 2023)
This research is motivated by the low ability of children to recognize number symbols in group A TK Dharma Wanita 1 Jurug Sooko. This is due to the lack of teacher skills and the proper media has not been used in introducing number symbols to children. This research was conducted to determine the increase in the ability to recognize children’s number symbols using loose parts media. This study used a Classroom Action Research (CAR) design with quantitative descriptive data analysis techniques using a paired sample t-test for two groups of data, namely the pre-test and post-test. Data collection techniques used are observation, documentation, and tests. The data analysis test in this study was carried out through several stages including the normality test and hypothesis testing stages. The data analysis test was carried out with the help of SPSS 18 and produced output data showing a significance value (2-tailed) of 0.000 <0.05, then H0 was rejected and Ha was accepted, so it can be concluded that there is a significant difference during the pre-cycle, cycle I, and cycle II. The pre-cycle average results, namely before being given action using loose part media of 4.6, the average value of cycle I increased to 5.733, and the average value of cycle II experienced a good increase of 6.8, so descriptively there was an increase the average of pre-cycle, cycle I and cycle II.